Optimization of Asset Recovery In Corruption Criminal Acts Through The Reversal Approach of Burden of Proof and In Rem Asset Forfeiture In Indonesia - Sendi Sanjaya; Rahmiati Rahmiati; Deddi Fasmadhy Satiadharmanto (Siber Nusantara Research, 2024)
Asset recovery from corruption in Indonesia presents a significant challenge for the legal system.(Ariawan, IGK (2008). Stolen Asset Recovery Initiative: A Hope in Returning State Assets. Kertha Patrika Journal, 33(1). Corruption not only undermines national finances but also threatens social and economic stability. In this context, the implementation of the reversal of the burden of proof and in rem asset forfeiture models is crucial for optimizing asset recovery. The reversal of the burden of proof shifts the responsibility to the perpetrators to demonstrate that the assets they hold are not derived from criminal activities. Meanwhile, in rem asset forfeiture allows the state to seize assets suspected of being the result of a crime without having to wait for a final legal ruling against the perpetrator. This approach provides an opportunity for the state to recover lost assets, even if the perpetrator cannot be conventionally punished. Through normative legal research, it is essential to explore the application of these two approaches within the Indonesian legal system. By analyzing various mechanisms and case studies, ways to accelerate the recovery of state losses can be identified. The findings indicate that the integration of the reversal of the burden of proof and in rem asset forfeiture can serve as an effective solution. This approach not only enhances the legal capacity for asset seizure but also delivers the necessary deterrent effects to reduce corrupt practices. Therefore, implementing these two models is vital to strengthening anti-corruption efforts in Indonesia.